1991
DOI: 10.3354/meps070039
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and the effects of competition on some temperate Scleractinia and Corallimorpharia

Abstract: The impact of interference competition on coral community structure is poorly understood. On subtidal rocks in the northeastern Pacific, members of 3 scleractinian coral species (Astrangia lajollaensis, Balanophyllia elegans, Paracyathus stearnsii) and 1 corallimorpharian (Corynactls californica) were examined to determine whether competition exerts substantial influence over t h e~r abundance and distributional patterns. These anthozoans occupy > 50 % cover on hard substrata, and exhibit characteristic patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
3

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 15 publications
0
27
0
3
Order By: Relevance
“…Previous studies have investigated competition processes among many invertebrates such as sponges (ABDO et al, 2008;LUTER;DUCKWORTH, 2010), ascidians (SHENKAR;SHENKAR et al, 2008), Bryozoans (TURNER;TODD, 1994) and cnidarians (LANG, 1973;JACKSON;BUSS, 1975;SHEPPARD, 1979SHEPPARD, , 1985KARLSON, 1980;SAMMARCO et al, 1985;SHEPPARD, 1985;DAI, 1990;ROMANO, 1990;CHADWICK, 1991;ALINO et al, 1992;FRANK et al, 1995;BASTIDAS;BONE, 1996; VAN VEGHEL et al, 1996;RINKEVICH;SAKAY, 2001;CONNELL et al,. 2004;RINKEVICH, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated competition processes among many invertebrates such as sponges (ABDO et al, 2008;LUTER;DUCKWORTH, 2010), ascidians (SHENKAR;SHENKAR et al, 2008), Bryozoans (TURNER;TODD, 1994) and cnidarians (LANG, 1973;JACKSON;BUSS, 1975;SHEPPARD, 1979SHEPPARD, , 1985KARLSON, 1980;SAMMARCO et al, 1985;SHEPPARD, 1985;DAI, 1990;ROMANO, 1990;CHADWICK, 1991;ALINO et al, 1992;FRANK et al, 1995;BASTIDAS;BONE, 1996; VAN VEGHEL et al, 1996;RINKEVICH;SAKAY, 2001;CONNELL et al,. 2004;RINKEVICH, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Differences among species of corals in tolerances to several physical factors (wave energy, currents, desiccation, light, temperature and sedimentation) are thought to determine the upper and/or lower limits of species depth distnbutions (Done 1982, Sheppard 1982, Sebens & Done 1992. Biological factors (competition and predation) have also been suggested as important controls on the depth distributions of corals (Glynn 1976, Sheppard 1982, Huston 1985, Chadwick 1991, although the widespread importance of biological controls for depth distributions of corals on tropical reefs has yet to be demonstrated. Previous attempts to unravel the processes underlying vertical zonation of tropical corals have focused primarily on factors affecting mature, coral populations (reviewed by Sheppard 1982), and with few exceptions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, biological interaction can alter local physical regimes which in turn can determine adult coral distribution. Other factors commonly recognized as determinants of coral recruitment are competition for space (Chadwick, 1991;Glynn, 1976;Sheppard, 1979), exogenous chemical signals (de Nys et al, 1991;Heyward and Negri, 1999;Koh and Sweatman, 2000), and disturbance by grazers (Lirman, 2001;Sammarco, 1980;Sammarco and Carleton, 1981). One of the few field experimental studies attempting to evaluate the importance of biological interactions on the sun coral distribution conducted in Brazil concluded that predation on Tubastraea spp.…”
Section: Introductionmentioning
confidence: 99%